He Āpiti Hono, He Tātai Hono: That Which is Joined Remains an Unbroken Line: Using Whakapapa (Genealogy) as the Basis for an Indigenous Research Framework - James Graham (The Australian Journal of Indigenous Education, 2005)
Abstract